SUSTAINING BATIK LASEM: GOVERNMENT POLICIES, WOMEN’S EMPOWERMENT, AND CENTRAL BANK SUPPORT - Nursanti, Tinjung Desy; Wiyarti, Evy Steelyana (Journal of Central Banking Law and Institutions, 2025)
This paper adopts a multifaceted approach to explore the interplay between government policies, the education system, women’s empowerment, and central bank intervention in the preservation of the Batik Lasem industry in Central Java, Indonesia. Utilising qualitative methodologies with content analysis techniques, the study addresses four key research questions: (1) protective measures for the industry; (2) educational contributions to sustainability and MSME support; (3) women’s empowerment within Batik Lasem MSMEs; and (4) the central bank’s role in market promotion and financial access. Findings reveal a complex landscape shaped by policies, the education system, entrepreneurial dynamics, and financial intervention. The study underscores the importance of collaborative efforts and strategic initiatives for fostering industry growth, cultural preservation, and gender equality. It recommends enhancing collaboration among all stakeholders, educational opportunities, gender-equitable policies, and continued support for the Batik Lasem industry. It highlights the potential for synergistic partnerships to further elevate the industry and empower its participants.